PENGARUH PEMASARAN MULTI-SENSORI TERHADAP NIAT BELI ULANG KONSUMEN DUNKIN DONUTS DI BANDAR LAMPUNG - Kurnia Prastyanti,; Roslina, Roslina; Dwi Asri Siti Ambarwati, (Nusantara Hasana Journal, 2025)
The current phenomenon is that according to the 2024 Top Brand Index Survey, in the last 5 (five) years Dunkin Donuts still ranks second from its competitors. In fact, if you look at it, the company has implemented multi-sensory marketing as a strategy to make customers have repeat purchase intentions. The purpose of this study itself is to find out whether Multi-Sensory Marketing (Sight, Smell, Taste, Sound & Touch) can influence consumer repeat purchase intentions. This study uses a quantitative approach obtained directly from respondents using a Google form questionnaire to 100 respondents with a 5-point Likert scale indicator. This study uses the SPSS analysis tool. The results of partial testing show that multi-sensory marketing variables (sight, smell, taste, sound & touch) have an effect on consumer repeat purchase intentions at Dunkin Donuts.